RNA Degradation in Staphylococcus aureus: Diversity of Ribonucleases and Their Impact - Rémy A. Bonnin; Philippe Bouloc (International Journal of Genomics)
The regulation of RNA decay is now widely recognized as having a central role in bacterial adaption to environmental stress. Here we present an overview on the diversity of ribonucleases (RNases) and their impact at the posttranscriptional level in the human pathogen Staphylococcus aureus. RNases in prokaryotes have been mainly studied in the two model organisms Escherichia coli and Bacillus subtilis. Based on identified RNases in these two models, putative orthologs have been identified in S. aureus. The main staphylococcal RNases involved in the processing and degradation of the bulk RNA are (i) endonucleases RNase III and RNase Y and (ii) exonucleases RNase J1/J2 and PNPase, having 5′ to 3′ and 3′ to 5′ activities, respectively. The diversity and potential roles of each RNase and of Hfq and RppH are discussed in the context of recent studies, some of which are based on next-generation sequencing technology.